Validity evidence for assessing social-emotional psychological strengths in Colombian adolescents using the SEHS-S - Diana Riaño-Hernández; Iwin Leenen; Angelli Ramírez-Conde; Paula A. Atehortua-Rivera; José A. Piqueras (PLoS ONE, 2025)
Background Covitality is a multidimensional hierarchical construct of core psychological strengths that synergistically promote resilience and well-being and that has been shown to be effective in preventing mental health problems in individuals of different age groups. The Covitality Model consists of 12 first-order latent factors, 4 second-order factors, and one general higher-order Covitality factor. Purpose In this study, we aim at obtaining validity evidence for the assessment of Covitality in Colombian adolescents by means of the Social Emotional Health Survey-Secondary (SEHS-S). Method A sample of 1461 adolescents responded the SEHS-S and four other instruments that measure well-being and distress. The internal structure of the SEHS-S was examined through confirmatory factor analyses as well as its relations with other variables. Results The hierarchical factor structure of the SEHS-S was supported (with goodness-of-fit statistics: χ2 = 1727.6, df = 578, p < .001; RMSEA = .037; SRMSR = .044; AGFI = .962; CFI = .940; and NNFI = .935) and configural and metric invariance across gender and age was confirmed; however, the assumption of scalar invariance across males and females and across age groups was violated for some items. Furthermore, we found moderate to high correlations (r = .56 –.68) of Covitality with related constructs. Conclusion As a conclusion, the SEHS-S can be considered a valid tool to assess psychological strengths, well-being, and resilience (i.e., Covitality) in Colombian adolescents, though further research is needed to explore the differences in item functioning across gender and age.